Global Liquidity Determinants Across Emerging and Advanced Countries - Renata Karkowska (Journal of Banking and Financial Economics)
The paper explores the concept of global liquidity and its determinants, focusing on the banking system in advanced and emerging markets. We explore the implications of the interaction between liquidity and its local, global and financial markets determinants. We also analyze the global liquidity channels, i.e. whether foreign banks play a significant role in the country’s financial system. The study focuses on the investigation of banks’ liquidity determinants in 42 countries (advanced and emerging/developing countries) over the 2000–2011 period. The results show the significance of the differences in global liquidity depending on the country’s level of development. We find support to the conjecture that globalization and global banks’ leverage may convey some useful information on global liquidity. We also present an important observation that banks’ lending in advanced countries is shielded from the monetary policy because of their ability to freely access alternative sources of funds.